Therapeutic Transactions for Medical Services through Online Clinics on A Legal Perspective - Indraswari, Sri Primawati; Sutrisno, Endang; Maulida, Irma; Karmenita, Karmenita (Green Publisher Indonesia, 2023)
The development of digitalization of almost all aspects of modern life, including healthcare, has been influenced by the use of technology. Health is very important for everyone, no matter age, socioeconomic status, or other factors. The current digital age in the provision of medical services through virtual clinics has grown rapidly. However, the existence of online clinics creates unclear legal regulations for therapeutic transactions, which can have potentially adverse legal repercussions for patients. Patients can file lawsuits against online clinics and healthcare professionals involved if there is an error in diagnosis or treatment. Therapeutic transactions consist of medication, diagnosis and medical treatment. But in online clinics, there is debate about the legality and ethics of these therapeutic transactions. Some of the problems that arise in therapeutic transactions through online clinics include the inability to perform physical examinations, medical data security issues, and the inability to track patient histories. The method used to assess is doctrinal (normative juridical), considering the concept of law as written law, which is made by local government regulations. The results showed that Health Law Number 36 of 2009 concerning Health and Article 1320 of the Civil Code, which regulates the legal terms of an agreement, can be used to assess the validity of therapeutic transactions carried out in online clinics. The research findings also show that fulfillment of the requirements of Health Law Number 36 of 2009 must include the responsibility of patients who receive medical care through online clinics. To optimize their services on online clinic platforms such as the Cirebon City Health Office, health service providers and health practitioners such as doctors, medical personnel, and other health workers use this platform. These organizers must consider Health Law Number 36 of 2009, which covers medical practice standards, telemedicine patient privacy, and a doctor's license or License to Practice. In addition, special policies must be made by the central government and the Cirebon City Health Office to provide clear legal protection for patients who receive medical services through online clinics when conducting medical transactions.